2022
DOI: 10.7759/cureus.21743
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Portal Vein Thrombosis in a Patient With Methylenetetrahydrofolate Reductase A1298C Polymorphism

Abstract: Portal vein thrombosis (PVT) is a prothrombotic state caused by blood flow stasis, vascular injury, and/or hypercoagulability, resulting in partial or complete occlusion of the portal vein. PVT is a rare diagnosis, particularly among those without liver disease. Typical risk factors for PVT include cirrhosis, hepatocellular carcinoma, myeloproliferative neoplasms, other malignancies, oral contraceptive use, bowel infections, and inherited hypercoagulable disorders. The goal of this study is to analyze a case o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A 2010 multicenter study suggested an incidence of 0.7 per 100 000 and a prevalence of 3.7 per 100 000 in developed countries, notably rising with cirrhosis or pro-thrombotic disorders. Cases involving individuals without cirrhosis are scarce, underscoring the significance of instances like the one presented 1 , 16 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2010 multicenter study suggested an incidence of 0.7 per 100 000 and a prevalence of 3.7 per 100 000 in developed countries, notably rising with cirrhosis or pro-thrombotic disorders. Cases involving individuals without cirrhosis are scarce, underscoring the significance of instances like the one presented 1 , 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Variceal eradication before anticoagulation is considered. Thrombolytic therapy and surgical interventions are considered in select cases when anticoagulation fails 1 , 2 , 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation